2008
DOI: 10.1007/s00018-008-7570-z
|View full text |Cite
|
Sign up to set email alerts
|

Entry of herpesviruses into mammalian cells

Abstract: The mechanism that herpesviruses use to enter cells is one of the most complex viral entry mechanisms studied so far. This complexity seems to mount as new participants, both cellular receptors and viral glycoproteins, are identified. Recent structural work on entry glycoproteins gD and gB from herpes simplex virus (HSV) 1 has illuminated the functional roles of these glycoproteins in the process of entry. In doing so, it provided information on the mechanism of two critical steps of HSV entry: receptor-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
311
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(318 citation statements)
references
References 151 publications
(145 reference statements)
4
311
0
3
Order By: Relevance
“…1A). Glycoprotein B (gB), one of the major envelope glycoproteins in herpesviruses, functions to facilitate attachment to host cell receptors and mediate fusion of the viral envelope with the host cell membrane (30). MAb 97.3 is a neutralizing monoclonal antibody raised against MCMV gB and is effective at preventing MCMV infection in vitro and in vivo (31).…”
Section: Electrochemical Detection Of Discrete CMV Collisionsmentioning
confidence: 99%
“…1A). Glycoprotein B (gB), one of the major envelope glycoproteins in herpesviruses, functions to facilitate attachment to host cell receptors and mediate fusion of the viral envelope with the host cell membrane (30). MAb 97.3 is a neutralizing monoclonal antibody raised against MCMV gB and is effective at preventing MCMV infection in vitro and in vivo (31).…”
Section: Electrochemical Detection Of Discrete CMV Collisionsmentioning
confidence: 99%
“…Similar to other herpesviruses, the envelope glycoproteins gB and gH/gL form the conserved fusion machinery required for viral entry (5,6). Recent structural and mutagenesis analysis suggested that gB is responsible for mediating virus and host membrane fusion during viral entry (7,8).…”
mentioning
confidence: 99%
“…It has been proposed that gH/gL is involved in the entry process through activation of gB (12). In addition to gB and gH/gL, most herpesviruses encode additional glycoproteins that are able to interact with gH/gL and are capable of either mediating binding to specific cellular receptors or regulating the activity of the gH/gL-gB complex (5,6).…”
mentioning
confidence: 99%
“…herpes simplex virus | glycoprotein | gH | gL | virus entry E ntry of herpesviruses into the cell is an orchestrated process that necessitates a multipartite glycoprotein system, rather than onetwo glycoproteins, as is the case for the vast majority of viruses (1)(2)(3)(4). For herpes simplex virus (HSV), the entry-fusion apparatus consists of four essential glycoproteins -gD, the heterodimer gH/gL, and gB-plus cognate cellular receptors.…”
mentioning
confidence: 99%